Effects of brief mindfulness training on basketball free-throw shooting performance under pressure: a randomized controlled trial of dosage response - Arthur-Cameselle, J. N.; Keeler, L. A. (Journal of Clinical Sport Psychology, 2025)
Studies have indicated that as little as 15 min of mindfulness training (MT) positively affects sport performance under pressure, but the minimum amount of MT required to induce effects is unclear. The current experiment tested the effects of MT of different lengths on free-throw shooting under pressure. Forty-six participants (78% men) with competitive basketball experience completed pretest mindfulness and anxiety surveys and shot under low pressure. Using performance-based matched assignment, participants were randomly distributed into groups. On another day, participants completed audio trainings (6-min MT, 15-min MT, or control) and then shot under high pressure. Under high pressure, anxiety and mindfulness states did not differ among groups, nor were there group differences in average shooting percentage. However, only the control group performed worse on the second shot under high pressure compared with low pressure, suggesting possible protection effects of MT. Findings are discussed regarding application and possible interactions between traits, motivation, and incentive values.